A Sourcebook of Classical Hindu Thought
This volume presents material drawn from the classical Hindu texts, as well as other sources, to familiarize readers with the outlines of classical Hindu thought. It provides a bunch of readings organized around certain set concepts, quarried from Hindu religious texts of thepast. It discusses material from classical Hindu texts relating to the themes of the divine realm such a brahman, devi, ishvara, trimurti, and so on, as well as of the mundane realm, such as jiva, samsara, karma, dharma, and so on. It also covers the concepts which link the two realms, such as those of maya, and the overcoming of it through yoga, to attain moksha. Some selections also throw light on what classical Hinduism has to say about the human being as a social being, through such concepts as varna, ashrama, and the purusharthas. The volume would be of interest to all students and scholars of Hinduism, and particularly those interested in exploring Hindu philosophy and theology